La Grève des forgerons de François Coppée, un arma antihuelga en los escenarios españoles (1890-1923) - Gérard Brey (Cahiers de Civilisation Espagnole Contemporaine)
This article analyses the way conservative circles, in their ideological fight against socialism and anarchism in the second half of the Spanish Restoration, resorted to an 1869 drama monologue by François Coppée which they viewed as an admonition that strikes bring about even graver consequences than the evils they purport to resolve.